Rhizospheric microorganisms: The gateway to a sustainable plant health - Dlamini, Siphiwe Prudence; Akanmu, Akinlolu Olalekan; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
Plant health is essential for food security, and constitutes a major predictor to safe and sustainable food systems. Over 40% of the global crops’ productions are lost to pests, insects, diseases, and weeds, while the routinely used chemical-based pesticides to manage the menace also have detrimental effects on the microbial communities and ecosystem functioning. The rhizosphere serves as the microbial seed bank where microorganisms transform organic and inorganic substances in the rhizosphere into accessible plant nutrients as plants harbor diverse microorganisms such as fungi, bacteria, nematodes, viruses, and protists among others. Although, the pathogenic microbes initiate diseases by infiltrating the protective microbial barrier and plants’ natural defense systems in the rhizosphere. Whereas the process is often circumvented by the beneficial microorganisms which antagonize the pathogens to instill disease resistance. The management of plant health through approaches focused on disease prevention is instrumental to attaining sustainable food security, and safety. Therefore, an in-depth understanding of the evolving and succession of root microbiomes in response to crop development as discussed in this review opens up new-fangled possibilities for reaping the profit of beneficial root–microbiomes’ interactions towards attaining sustainable plant health.